PERSIS: Manual de Referencia - Vogt, Ada; Suter,Tito; Arregui, Elena; Gutiérrez, Elsa (Comisión Nacional de Energía Atómica (CNEA), 1988)
Fil:Vogt, Ada Comisión Nacional de Energía Atómica (CNEA). República Argentina